METODOLOGIA EXPERIMENTAL PARA AVALIAÇÃO DO DESEMPENHO DE VÁLVULAS DE SEGURANÇA PARA AR COMPRIMIDO E CONTRAPRESSÃO ATMOSFÉRICA - Anna, Thiago de Freitas Hulle Sant (2021)
The safety of devices and equipment subjected to pressure is directly associated with the dimensioning and correct functioning of a safety valve. For that, it is necessary to evaluate its performance. This work develops and tests methodologies for flow te